Viscachataenia quadrata Denegri, Dopchiz, Elissondo & Beveridge, 2003 (Cestoda: Anoplocephalidae) in Peru - Tantaleán, Manuel (2009)
We are identified to Viscachataenia quadrata Denegri, Dopchiz, Elissondo & Beveridge, 2003 of the small intestine of Lagidium peruanum Meyen, from Lima, Puno and Ayacucho.